PENGARUH PENGETAHUAN TENTANG MENOPOUSE DENGAN KECEMASAN MENGHADAPI MENOPOUSE PADA WANITA DI KELURAHAN SUMBER SURAKARTA - Rusmeirina, Cepty (Universitas Sahid Surakarta, 2014)
Menopause is a natural phase that will be faced by women over the age of 40years. Where does this mark the end of a womans fertile period. Menopausal syndromeexperienced by many women because it takes an understanding. The purpose of this studywas to determine the presence or absence of knowledge about the effects of menopausewith anxiety facing menopause in women. The population in this study were all women aged 40 years - 65 years in the Village Source Surakarta. The sampling technique usedwas simple random sampling. The study was conducted using primary data andsecondary data. Analysis of the data in this study consists of two parts: a descriptive andcorrelational analysis. Based on the data analysis it can be concluded that there is a significant positive relationship between knowledge of menopause in women with anxiety is r = 0.729; p =0.000 (p <0.05), which means that the higher the level of knowledge about menopause, the lower the anxiety levels of women in the Source Surakarta. Effective contribution tothe variable knowledge about menopause anxiety by 53.1% indicated the determinant coefficient (r2) of 0.531. Meanwhile, 46.9% influenced by other factors such as family support, social-economic, cultural and lifestyle characteristics.